Counseling Supporting HIV Self-Testing and Linkage to Care Among Men Who Have Sex With Men: Systematic Review and Meta-Analysis - Siyu Chen; Yuan Fang; Paul Shing-fong Chan; Joseph Kawuki; Phoenix Mo; Zixin Wang (JMIR Publications, 2024)
BackgroundCounseling supporting HIV self-testing (HIVST) is helpful in facilitating linkage to care and promoting behavior changes among men who have sex with men (MSM). Different levels of counseling support for MSM HIVST users may lead to variance in the linkage to care. ObjectiveThis study aims to synthesize evidence on counseling supporting MSM HIVST users and to conduct a meta-analysis to quantify the proportion of MSM HIVST users who were linked to care. MethodsA systematic search was conducted using predefined eligibility criteria and relevant keywords to retrieve studies from the MEDLINE, Global Health, Web of Science, Embase, APA PsycINFO, and Scopus databases. This search encompassed papers and preprints published between July 3, 2012, and June 30, 2022. Studies were eligible if they reported counseling supporting HIVST or quantitative outcomes for linkage to care among MSM and were published in English. The screening process and data extraction followed the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) guidelines. The quality of the included studies was assessed by the National Institutes of Health quality assessment tool. Data were extracted using random effects models to combine the proportion of HIVST users who were linked to care. Subgroup analyses and metaregression were conducted to assess whether linkage to care varied according to study characteristics. All analyses were performed with R (version 4.2.1; R Foundation for Statistical Computing) using the metafor package. ResultsA total of 55 studies published between 2014 and 2021, including 43 observational studies and 12 randomized controlled trials, were identified. Among these studies, 50 (91%) provided active counseling support and 5 (9%) provided passive counseling support. In studies providing active counseling support, most MSM HIVST users were linked to various forms of care, including reporting test results (97.2%, 95% CI 74.3%-99.8%), laboratory confirmation (92.6%, 95% CI 86.1%-96.2%), antiretroviral therapy initiation (90.8%, 95% CI 86.7%-93.7%), and referral to physicians (96.3%, 95% CI 85%-99.2%). In studies providing passive counseling support, fewer MSM HIVST users were linked to laboratory confirmation (78.7%, 95% CI 17.8%-98.4%), antiretroviral therapy initiation (79.1%, 95% CI 48.8%-93.7%), and referral to physicians (79.1%, 95% CI 0%-100%). Multivariate metaregression indicated that a higher number of essential counseling components, a smaller sample size (<300), and the use of mobile health technology to deliver counseling support were associated with better linkage to care. The quality of the studies varied from fair to good with a low to high risk of bias. ConclusionsProactively providing counseling support for all users, involving a higher number of essential components in the counseling support, and using mobile health technology could increase the linkage to care among MSM HIVST users. Trial RegistrationPROSPERO CRD42022346247; https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=346247